Proposed Marketing Strategy to Improve Customer Loyalty of Brand XYZ - Made Sri Ayu Apsari; Nita Garnida; Prawira Fajarindra Belgiawan (UNIVED Press, 2024)
This research aims to provide strategies to increase customer loyalty from brand XYZ. This research was conducted using the variables brand image, customer involvement, and customer satisfaction. Internal analysis using Marketing Mix, STP, and VRIO as well as external analysis, namely PESTLE, Porter's Five Forces, Competitor Analysis, and Customer Analysis in this research are used to find out what the internal and external conditions of brand XYZ are. In this research, primary data and secondary data are used to support the analysis to be carried out. The primary data used was obtained from interviews with brand XYZ, as well as questionnaire surveys distributed to brand XYZ customers which will then be processed using Structural Equation Modeling Partial Least Square (SEM PLS). Secondary data is used in this research to support analysis in the form of theory from sources relevant to this research. The results of internal and external analysis as well as the results of the hypothesis in this research are that brand image and customer engagement have a significant and positive influence on customer loyalty, but customer satisfaction does not have a significant influence on customer loyalty. Based on the results of the analysis that has been carried out, a marketing strategy recommended by the author to increasing customer loyalty.